2016
DOI: 10.5152/balkanmedj.2016.150529
|View full text |Cite
|
Sign up to set email alerts
|

Domestically Acquired Legionnaires’ Disease: Two Case Reports and a Review of the Pertinent Literature

Abstract: Background: Legionella species may colonize in home water systems and cause Legionnaires' disease (LD). We herein report two cases of sporadic LD associated with the solar energy-heated hot water systems of the patients' houses. Case Report: A 60-year-old woman with chronic bronchitis and diabetes mellitus presented with a high fever, abdominal pain, and diarrhea. Physical examination revealed rales, and her chest radiograph showed a homogeneous density in the left lung. The Legionella urinary antigen test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A difference between our previous study [ 8 ] and these data concerns the type of hot water production. In this study, an higher risk of Legionnaires disease has been observed in residential buildings with solar thermal systems.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…A difference between our previous study [ 8 ] and these data concerns the type of hot water production. In this study, an higher risk of Legionnaires disease has been observed in residential buildings with solar thermal systems.…”
Section: Discussionmentioning
confidence: 64%
“…In fact, we detected Legionella spp. in 26% of apartments in buildings provided with a centralized or independent warm water production [ 8 ]. Considering only the solar thermal systems for hot water production, the positivity percentage was higher (40%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last three years an increase of literature data on Legionella spp. presence in water networks of residential buildings, has been observed [7,8,9,10,11]. Moreover, both an Italian guideline for Legionnaires' disease control in hospital and community settings, and the Drinking Water Directive identify the responsibilities for water quality control also in private residential buildings [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after this epidemic, an outbreak of hospital-acquired Legionnaires' disease was reported [5] . This was followed by the discovery of Legionella bacterial colonization of water systems used in the homes of patients with community-acquired Legionnaires' disease, demonstrating what a widespread and significant health problem Legionella infections were [6,7] . In Turkey, Legionnaires' disease was added to the list of notifiable diseases in 1996 and special surveillance for travel-associated cases was initiated with the Legionnaires' Disease Control Program [8,9] .…”
Section: Introductionmentioning
confidence: 99%